SENP2 Reduces Hepatocellular Carcinoma Stemness and Improves Sorafenib Sensitivity Through Inactivating the AKT/GSK3β/CTNNB1 Pathway - Tang, Xiaohui; Liu, Bohao; Zhang, Chen; Tang, Wenbin; Liang, Shitian; Xiao, Yadan; Deng, Ruoyu; Li, Zhuan (Frontiers in Oncology, 2021)
Background Small ubiquitin-like modifier specific peptidase 2 (SENP2) suppresses the progression and chemoresistance of several cancers, while few studies report its role in hepatocellular carcinoma (HCC). This study aimed to evaluate the effect of SENP2 on stemness, sorafenib sensitivity, and downstream pathway in HCC, with validation of its molecular mechanisms by compensation experiment. Methods SENP2 was regulated by plasmid transfection; meanwhile, in a compensation experiment, protein kinase B (AKT) was activated by SC79 treatment and β-catenin (CTNNB1) was overexpressed by plasmid transfection. After modification, sorafenib sensitivity was detected by cell counting kit-8 assay; stemness was evaluated by CD133+ cell proportion and sphere formation assay. Results SENP2 was decreased in HCC cell lines (including Hep3B, Li7, and Huh7) compared with normal human liver epithelial cell lines, which was further reduced in HCC stem cells than in normal HCC cells. Subsequently, SENP2 overexpression inhibited CD133+ cell proportion, decreased sphere formation ability, promoted sorafenib sensitivity, suppressed AKT and glycogen synthase kinase-3β (GSK3β) phosphorylation, and reduced CTNNB1 expression in Huh7 and Hep3B cells, while SENP2 knockdown showed the reverse effects. The following compensation experiment revealed that activating AKT or overexpressing CTNNB1 promoted CD133+ cell proportion and sphere formation ability but suppressed sorafenib sensitivity in Huh7 and Hep3B cells. Moreover, activating AKT or overexpressing CTNNB1 attenuated the effect of SENP2 overexpression on stemness and sorafenib sensitivity in Huh7 and Hep3B cells. Conclusion SENP2 suppresses HCC stemness and increases sorafenib sensitivity through inactivating the AKT/GSK3β/CTNNB1 signaling pathway.